2016
DOI: 10.4067/s0718-95162016005000031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saline irrigation water on the leachability of salts, growth and chemical composition of wheat (Triticum aestivum L.) in saline-sodic soil supplemented with phosphorus and potassium

Abstract: Salinity-fertility interaction has not been properly explored especially in saline-sodic soils. Therefore, the current study investigated the response of wheat (Triticum aestivum L.) to saline irrigation water in salinesodic soil supplemented with potassium (K) and phosphorus (P). Wheat was grown in pots filled with salinesodic soil which were irrigated either with normal or saline water. Potassium and P fertilizers were applied at two levels. Results indicated that growth of wheat plants was impaired by salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 24 publications
3
28
0
Order By: Relevance
“…Salinity is one of the most important environmental stresses, which noticeably hinders crop productivity in many arid and semi-arid regions (Torbaghan et al, 2017). Low precipitation, high surface evaporation, poor cultural practices and irrigation with saline water are among the major contributors to the increasing salinity problems (Hussain et al, 2016). In general, a group of morphological, physiological and biochemical changes in the plant growth are caused by soil salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity is one of the most important environmental stresses, which noticeably hinders crop productivity in many arid and semi-arid regions (Torbaghan et al, 2017). Low precipitation, high surface evaporation, poor cultural practices and irrigation with saline water are among the major contributors to the increasing salinity problems (Hussain et al, 2016). In general, a group of morphological, physiological and biochemical changes in the plant growth are caused by soil salinity.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the water quality affected crop harvest index when water was applied at the flowering stages (Table 6). Previous studies reported that saline water irrigation reduced water uptake efficiency, transpiration rate and net CO 2 assimilation due to these reductions, and in turn crop growth and nutrients transport into plant is affected [72][73][74][75]. Similarly, Poustini [76] reported that there was no effect of water quality having an EC 1:5 ranging between 3.5 and 6.9 dS m −1 on net assimilation rate.…”
Section: Discussionmentioning
confidence: 95%
“…Calcium and magnesium in root tissue were affected significantly by the phosphorus with potassium interactions. EC i x P w x potassium interaction didn't effect on all other parameters, except Mg in shoot and Ca and Mg in root tissue by [81].…”
mentioning
confidence: 80%